“It took a village” - Stories from students in the social sciences about learning quantitative methods - Jully Paola Merchán Tamayo; Simon G. Beaudry; Dominique Gagnon; Nada Nasser; Meredith A. Rocchi (Journal of Statistics and Data Science Education, 2025)
For most undergraduate students studying in fields without a focus on statistics or data science (i.e., non-majors), their only opportunity to acquire these in-demand data analysis skills is in their required quantitative methods course. These courses generally have a bad reputation among students who do not see how the course fits within their program. There have recently been improvements to these courses; however, the negative perceptions persist. The objective of this research was to examine the experiences of non-major students during their introductory quantitative methods course with the goal of understanding how these courses are experienced and can continue to be improved. A narrative-based approach was used with 11 non-major undergraduate students at the end of their studies (third, fourth and sixth year) who participated in semi-structured interviews where they told stories about their quantitative methods course. A thematic analysis which identified six main themes was conducted, and the results are presented using 4 turning-points (before the class, before the middle of the course, before the final, and after the class). The results provided insight about how these courses are experienced and the findings are discussed in terms of potential opportunities for improvement in these courses moving forward.